Fatigue life optimization towards rubber core sealing surface of under-balanced drilling rotating blowout preventer. (November 2020) - He, Yuhang; Fan, Yu; Wu, Pengcheng; Xia, Chengyu; Huang, Jian; Wu, Jiwei; Qian, Liqin; Liu, Xianming
Highlights: Rotary blowout preventer is the key equipment of underbalanced drilling. The rubber core is prone to failure when subjected to alternating cycle load. Simulate the rubber core sealing process based on finite element method. Optimize the structure of rubber core and safe lower speed of drill pipe. The optimized rubber core was verified in laboratory and field experiments. Abstract: In the process of under-balanced drilling, the rubber core of rotating blowout preventer (RBOP) subject to the alternating cycle load was prone to fatigue failure. Firstly, the sealing principle of RBOP was analyzed and the stress of rubber core in dynamic sealing process was obtained. Then, the Yeoh constitutive model in the deformation process was established by the tensile test of the rubber core material. Then we used ABAQUS software to establish the finite element model of the dynamic sealing of the rubber core, and the simulation of the sealing process of the rubber core during the drilling and tripping operations and the optimization analysis of the factors affecting the fatigue life of the sealing surface of the rubber core were carried out. In this paper, the structure of the rubber core was optimized, and the optimal outer angle of the rubber core was 155°, the inner angle was 153°, and the base angle was 125°. Then the inner diameter size of rubber core that was matched with different outer diameter drill pipes was optimized and the best combination of rubber core was obtained. The paper also optimized the lowering and lifting speed of drill pipe under different wellhead pressures. The higher the well pressure, the more likely the rubber core fatigue failure would be. The safe lowering and lifting speed of drill pipe under different pressures was obtained. At last, according to the Chinese standard, indoor seal test and field application test were carried out in the Well Control Equipment Quality Supervision and Inspection Center of China national petroleum industry to confirm the reliability of finite element optimization, which was of great practical significance to improve the service life of rubber core and oilfield operation safety.